2016
DOI: 10.1186/s40981-016-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

Successful perinatal management of a ruptured brain arteriovenous malformation in a pregnant patient by endovascular embolization followed by elective cesarean section: a single-case experience

Abstract: BackgroundAlthough brain arteriovenous malformations (AVM) usually remain asymptomatic during pregnancy, they can cause intracranial hemorrhage and lead to serious neurological deficits. Nowadays, it is accepted that treatment of a ruptured brain AVM during pregnancy should be based on neurologic, not obstetric, indications.Recently, endovascular treatment has been recognized as a treatment option associated in pregnant patients with brain AVMs.Case presentationA 34-year-old woman presented at 25 weeks of gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Considering that the fetus is not in the directly irradiated area and shield protection is used, it is only exposed to scattered radiation. Our calculated fetal radiation dose of 0.02 mGy during diagnostic angiography and therapeutic endovascular procedure, confirmed the relatively low dose to the fetus under appropriate shielding protection of the uterus and is similar to fetal radiation doses previously calculated by other interventionalists [ 22 , 23 ]. Assuming that the cumulative fetal radiation dose should never exceed 100 mGy [ 20 ], endovascular procedures can be performed safely in pregnant patients.…”
Section: Discussionsupporting
confidence: 87%
“…Considering that the fetus is not in the directly irradiated area and shield protection is used, it is only exposed to scattered radiation. Our calculated fetal radiation dose of 0.02 mGy during diagnostic angiography and therapeutic endovascular procedure, confirmed the relatively low dose to the fetus under appropriate shielding protection of the uterus and is similar to fetal radiation doses previously calculated by other interventionalists [ 22 , 23 ]. Assuming that the cumulative fetal radiation dose should never exceed 100 mGy [ 20 ], endovascular procedures can be performed safely in pregnant patients.…”
Section: Discussionsupporting
confidence: 87%
“…Extremely limited information on the dose of fetal radiation during embolization is available in the literature. Asano et al reported an exposure level of the uterus of 0.14 mGy [63]. Although three feeding branches were embolized in our case in one session to achieve complete occlusion of the AVM, the dose in the uterus was less than 1 µSv.…”
Section: Discussionmentioning
confidence: 58%
“…However, the majority of large epidemiological studies of intracerebral haemorrhage in pregnancy have not been differentiated by mechanism. Risk of re-bleeding in the same pregnancy is 27%–30% which is much higher than women who are not pregnant within a year 1 3 4 8 9…”
Section: Discussionmentioning
confidence: 99%
“…Ruptured AVM has been successfully being treated by surgical resection 3 15. Direct open surgery is considered to be associated with a lower rate of feto-maternal mortality when compared with conservative management alone, however, it is associated with an elevated risk of intraoperative bleeding which causes a decrease in uterine and placental blood supply and hence risk to fetus 4. Non-surgical options like endovascular embolisation have shown promising results in many case reports 1 4 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation